Preparation of chiral acid-functionalized Schiff-base ligands and their complexation with divalent transition metals: the story of Helices and Cubanes - Lalehzari, Azadeh (Kansas State University, 2007)
A series of chiral symmetrical and unsymmetrical acid-functionalized Schiff-base ligands were synthesized by condensation reactions between 3-formyl salicylic acid and the two diamines (1R,2R)-cyclohexyldiamine (CHDA) and (R)-[1,1'-binapthalene]-2,2'-diamine (BINAM). The addition of a weak base (TEA) to these Schiff-bases resulted in the formation of a partially deprotonated ligand while the addition of the strong base NaOMe, resulted in fully deprotonated ligands. Complexations were carried out using metal salts of Fe(II), Co(II), Ni(II), Cu(II), Cu(I) and Zn(II). The partially deprotonated unsymmetrical Schiff-base (CHDA as the backbone), resulted almost exclusively in the formation of double-stranded helices with M helices. The fully deprotonated ligand, on the other hand, formed cubane-type structures with Fe(II), Co(II) and Ni(II) in methanol. Similar cubane-type structures were also obtained after complexation of the symmetrical CHDA-based ligands with Fe(II) and Co(II) using NaOMe in methanol. Reactions involving Cu(II) and Cu(I) salts resulted in either mono-or dinuclear salen complexes, even if the unsymmetrical Schiff-base was used as the starting ligand. This type of ligand conversion is dependent of the metal salt concentration in the reaction. Unsymmetrical Schiff-base ligands have a higher tendency to undergo conversion to their symmetrical salen analogues if the metal salt is added is much excess.
Keywords: Schiff-base; Helices; Cubanes; Chemistry, Inorganic (0488)